Discrimination, narratives and family history: An experiment with Jordanian host and Syrian refugee children - Kai Barron; Heike Harmgart; Steffen Huck; Sebastian Schneider; Matthias Sutter (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2020)
We measure the prevalence of discrimination between Jordanian host and Syrian refugee children attending school in Jordan. Using a simple sharing experiment, we find only little discrimination. Among the Jordanian children, however, we see that those who descended from Palestinian refugees do not discriminate at all, suggesting that a family history of refugee status can generate solidarity with new refugees. We also find that parents' narratives about the refugee crisis are correlated with the degree of discrimination, suggesting that discriminatory preferences are being transmitted through parental attitudes.
Keywords: C91; D90; J15; C93; J13; 330; discrimination; refugees; children; experiment; integration